ACTIVITY OF WOMEN IN SCIENCE, ADVANCED FOREIGN EXPERIENCES - Khurshida Tokhirovna Komilova (Journals Park Publishing, 2024)
The article analyzes the activities of women and girls in the fields of science, and highlights the ideas of the advanced research of women scientists around the world. The contribution of women to science, the results of the analysis of the activities of women in various fields of science are highlighted. The role of education and science in the life of women in the field of science, its influence on socialization, and the social image of women in the field of science are highlighted. The activity of women in the fields of science is disclosed.
Keywords: science, women, doctorate, scientist, research, scientific degree, scientific article, project, intellect, award, rating, experience of foreign countries, engineering.